Empowerment Program Toward Risk Behaviour Among Adolescent - Hadiyani, Wini; Sugianti, Nella (KnE Life Sciences, 2021)
Adolescence is recognized as a time of increased risk-taking compared with other age groups. The purpose of this study was to review previous journals related to empowerment program toward risk behaviors among adolescent. This study was a literature review as a method of collecting, analyzing a previous studies. Searching strategy was carried out electronically for several journal sites published between 2014-2019. We collected the journals from the databases PubMed, and Google scholar and reported according to the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA; Moher, Liberati, Tetzlaff, Altman, & The PRISMA Group, 2009). The results of the assessment using the JBI format. There are five articles reviewed empowerment stating that empowerment influence family and community support factors the adolescent empowerment program has a role on self-esteem, reducing depression, smoking, drug use, and prevention of sexual behavior. Empowerment programs in adolescents impact risky behavior such as reproductive health, HIV prevention, drug / alcohol and smoking by increasing reinforcement of knowledge, peer collaboration and opportunities for self-development. Keywords: adolescent, empowerment, risk behavior